Ethical culture and health research - Rodríguez Yunta, Eduardo (Acta Bioethica, 2005)
This paper argues about the importance of developing an ethical culture, particularly in developing countries, so that international health research would be carried out ethically; and about the role of bioethics exercising a transdisciplinary dialogue in the analysis of social context and in promoting equity in both the selection of research subjects and the distribution of research benefits.